Key technologies research on of soil-structure interaction base story isolated structure response in 3D seismic zone - Xu, Jingran; Gao, Haolun; Guo, Zihan; Zhao, Jie; Yang, Zhuoxin; Zhao, Guangxing; Guo, Zhongfa; Liu, Dewen; Sun, Weiwei (Frontiers in Earth Science, 2023)
The development of karst in Karst area leads to poor stability of stratum. If earthquake occurs, the area will produce destructive disaster. In order to improve the stability capacity of the grassroots in the region, this study investigates the seismic response of inter-story isolation structures considering soil-structure interaction (SSI) in three-dimensional earthquakes. A model of the inter-story isolation structure incorporating SSI was developed, and one-dimensional, two-dimensional, and threedimensional ground motions were applied to compare the seismic response under different input conditions. A three-dimensional isolation system was introduced and compared with traditional horizontal isolation structures to address excessive tensile and compressive stresses on the isolation structure during three-dimensional ground motion. The results demonstrate that the seismic response to three-dimensional earthquakes surpasses one-dimensional and two-dimensional inputs. Furthermore, adding a three-dimensional isolation structure effectively isolates vertical ground motion and reduces structural seismic response. Moreover, it minimizes soil stresses on the foundation compared to traditional horizontal isolation structure, enhancing foundation stability. This study will provide theoretical value and practical guidance for the research on key technology of SSI base story isolation structure response in Karst Plateau 3D Seismic zone.